Effect of Oxidation at Low Temperature on Thermal Dynamics Activation Energy of Lignite - Shao, Qun; Kong, Lingpo; Xu, Hui; Li, Sen (Asian Journal of Chemistry, 2013)
In this paper, on the basis of the effect of natural oxidation of lignite in air on coal characters, TG-DSC was performed to analyze oxidation stages and thermal dynamic parameters of original and naturally oxidized for different time lignite. The results showed the TGA and DSC curves of coal samples with low metamorphosed degree testified the five stages during lignite oxidation at low temperature and change of curves at characteristic spots reflected physical adsorption, chemical adsorption and process of chemical reaction and molecular structural conversion in coal. In comparison to that of original coal samples, the dynamics was discussed in different transformation ratio region and mechanism function and thermal dynamic parameters of oxidization pyrolysis process of coal were worked out through Coats Redfern integral method. The activation energy of lignite is low to -27.439 kJ/mol, resulting in coal samples were easy to be oxidized and after oxidation it could be increased by 39.07 kJ/mol. The above finding revealed that the oxidized lignite needed more energy to get to activated state.